Piano Sonata no. 7, op. 10, no. 3, in D major, edited by Jules Benedict - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Benedit, Jules, 1804-1885:::Contributor:::::::::::: (United Kingdom; London; Addison & Co., 2024)
Edition of the Piano Sonata no. 7, op. 10, no. 3, edited and fingered by Jules Benedict and published as part of the series "Jules Benedict's Edition of Pianoforte Works" by Addison & Co. in London.